Touring theatrical productions an international guide - Yadav, Dinesh (Routledge, 2023)
"Touring Theatrical Productions: An International Guide is a practical and comprehensive overview of planning, staging and closing international touring productions. This book offers a step-by-step chronological journal of preparing a company for international touring, from applying for international visas to returning home after a tour. It includes discussions of invitations, contracts, scheduling, health and safety, personnel, packing and shipping, certifications, insurance, travel, unions, hotels, ethics and cuisines. Each chapter is filled with guidelines, samples of paperwork, and checklists to ensure the smooth running of any international tour. Written by the Production Manager and Technical Director of India's most travelled show "The Manganiyar Seduction" with Can & Abel Theatres, the book includes examples, incidents and experiences of performing in over twenty countries with over two hundred shows. This how-to guide will benefit Technical Directors and Production Managers of touring productions, as well as students in Production Management, Tour Management, Art Administration and Technical Theatre courses"--